Output feedback image-based visual servoing of rotorcrafts - Li, Jianan (2019)
This paper presents an improved output feedback based image-based visual servoing (IBVS) law for rotorcraft unmanned aerial vehicles (RUAVs). The control law enables a RUAV with a minimal set of sensors, i.e. an inertial measurement unit (IMU) and a single downward facing camera, to regulate its position and heading relative to a planar visual target consisting of multiple points. As compared to our previous work, twofold improvement is made. First, the desired value of the image feature of controlling the vertical motion of the RUAV is a function of other image features instead of a constant. This modification helps to keep the visual target stay in the camera’s field of view by indirectly adjusting the height of the vehicle. Second, the proposed approach simplifies our previous output feedback law by reducing the dimension of the observer filter state space while the same asymptotic stability result is kept. Both simulation and experimental results are presented to demonstrate the performance of the proposed controller.